Estimation of Engel curves for household expenditure on dry bean and processed bean in Mexico - Antonio AGUILAR-LOPEZ; Salvador GONZÁLEZ-ANDRADE; Aleš KUHAR (Acta Agriculturae Slovenica)
Dry bean is the leading source of low-cost plant-based proteins in Mexico. However, in the years following the liberalization of the economy, Mexico experienced the erosion of a self-sufficiency index for this commodity. Impending changes in the international markets for proteins compel us to reevaluate the role of dry bean for Mexico’s food security. In the present paper we set out to analyze the last link of the marketing chain in Mexico’s dry bean market: the consumer. Using data on household expenditure for 2018, the relationship between income and expenditure on dry bean as well as on processed bean is ascertained by means of the Working-Leser Engel Curve equations system. Due to the presence of zero-expenditure households in the sample, we followed the two-step Heckit procedure for the possible selection bias. The results suggest that the budget share for dry bean and for processed bean drops as income increases. The corrected conditional elasticity for dry bean is −0.1056. For processed bean, the elasticity is −0.2286. The negative sign indicates that both commodities are inferior goods.